Factors That Mattered in Helping Travelers From Countries With Ebola Outbreaks Participate in Post-Arrival Monitoring During the 2014-2016 Ebola Epidemic - Christine E. Prue PhD; Peyton N. Williams MPH; Heather A. Joseph MPH; Mihaela Johnson PhD; Abbey E. Wojno PhD; Brittany A. Zulkiewicz BS; John Macom MPH; Jennifer P. Alexander MSW, MPH; Sarah E. Ray MA; Brian G. Southwell PhD (SAGE Publishing, 2019)
During the 2014-2016 Ebola epidemic in West Africa, the US Centers for Disease Control and Prevention (CDC) developed the CARE+ program to help travelers arriving to the United States from countries with Ebola outbreaks to meet US government requirements of post-arrival monitoring. We assessed 2 outcomes: (1) factors associated with travelers' intention to monitor themselves and report to local or state public health authority (PHA) and (2) factors associated with self-reported adherence to post-arrival monitoring and reporting requirements. We conducted 1195 intercept in-person interviews with travelers arriving from countries with Ebola outbreaks at 2 airports between April and June 2015. In addition, 654 (54.7%) of these travelers participated in a telephone interview 3 to 5 days after intercept, and 319 (26.7%) participated in a second telephone interview 2 days before the end of their post-arrival monitoring. We used regression modeling to examine variance in the 2 outcomes due to 4 types of factors: (1) programmatic, (2) perceptual, (3) demographic, and (4) travel-related factors. Factors associated with the intention to adhere to requirements included clarity of the purpose of screening ( B = 0.051, 95% confidence interval [CI], 0.011-0.092), perceived approval of others ( B = 0.103, 95% CI, 0.058-0.148), perceived seriousness of Ebola ( B = 0.054, 95% CI, 0.031-0.077), confidence in one's ability to perform behaviors ( B = 0.250, 95% CI, 0.193-0.306), ease of following instructions ( B = 0.053, 95% CI, 0.010-0.097), and trust in CARE Ambassador ( B = 0.056, 95% CI, 0.009-0.103). Respondents' perception of the seriousness of Ebola was the single factor associated with adherence to requirements (odds ratio [OR] = 0.81, 95% CI, 0.673-0.980, for non-adherent vs adherent participants and OR = 0.86, 95% CI, 0.745-0.997, for lost to follow-up vs adherent participants). Results from this assessment can guide public health officials in future outbreaks by identifying factors that may affect adherence to public health programs designed to prevent the spread of epidemics.